ERGONOMIC RISK ANALYSIS AND MUSCULOSKELETAL DISORDERS (MSDs) ON OPERATOR UNIFORMITY FINAL INSPECTION - Mariyatul Qibtiyah (Muhammadiyah International Public Health and Medicine Proceeding, 2022)
One of the occupational diseases in the workplace is related to ergonomics, ergonomics factors are very important to prevent work-related diseases and incidents. Disorders arising from inappropriate ergonomics affect the musculoskeletal system, Musculoskeletal disorders (MSDs), namely disorders of body structures such as muscles, joints, tendons, ligaments, nerves, cartilage, bones, and the local blood circulation system. This study aims to analyze the ergonomic risks and MSDs in workers. The population is all uniformity operators totaling 203 employees. The sample that met the inclusion criteria is 93 operators. The ergonomic risk was assessed based on the REBA sheet, and MSDs using the Nordic Body Map. Data were analyzed using the chi-square test. The results showed the level of risk in the booking process is 'high' (score 8); input uniformity is 'medium' (score 6), uniformity output is 'medium' (score 7) and the balancing process is 'medium' (score 6). Uniformity final inspection operators have MSDs are 88 peoples (94.62%) and did not has MSDs are 5 peoples (5.38%). Statistical test results show that there is no relationship between age, years of service, and education on MSDs operator Uniformity Final Inspection. Suggestions for research are providing lifting aids, job training or training on ergonomic risks and safe working procedures according to ergonomic principles, and work in accordance by power zone. providing personal protective equipment such as back support and setting appropriate working time and rest hours.